PENGARUH TABUNGAN DAN DEPOSITO MUDHARABAH TERHADAP SISA HASIL USAHA KOPERASI PEGAWAI NEGERI SYARIAH - RIZAL RIZAL (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2018)
The purpose of this research was to analyze the effect of hajj saving, qurban saving, wadiah saving and mudharabah deposit simultaneously and partially towards net income (SHU) of sharia civil servant cooperative Al-Ikhlas in IAIN Batusangkar. The type of this research was a field research through quantitative method with the secondary data used are the financial statements of the year 2015-2016. The result of this research provides the effect of deposit, qurban saving, wadiah saving and hajj saving simultaneously towards net income (SHU) is 62.7 % while the remaining 37.3% is influenced by other factors that not examined in this research. Partially, merely hajj saving that has positive and significant effect towards net income (SHU). While, qurban saving, wadiah saving and mudharabah deposit have no positive and significant effect towards net income (SHU).